2019
DOI: 10.22463/0122820x.1839
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Acidithiobacillus ferrooxidans, Acidithiobacillus thiooxidans and Leptospirillum ferrooxidans strains on sphalerite concentrate from mining waste

Abstract: One of the main characteristics of the microorganisms used in the leaching process is their capacity to adapt to aggressive environments, characterized by a notable presence of heavy metals. In this study the adaptation of the strains Acidithiobacillus ferrooxidans, Acidithiobacillus thiooxidans and Leptospirillum ferrooxidans was evaluated on a sphalerite concentrate from mining waste. In the adaptation tests, the energy source (ferrous sulphate) was gradually replaced by percentages of mineral pulp, ending w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The goals of this experiments were: (I) the determination of the ideal sulfur concentration to cover the microorganisms' necessities and, therefore, produce the highest amount of sulfuric acid, and (II) the leaching of the highest achievable zinc share while obtaining the lowest possible remaining sulfur in the already treated solid residue. Since the exposure of the microorganisms to a residue could possibly affect the microorganisms [22], batch experiments were conducted with (10, 30, 40 and 50 g/L) in 250 mL shaker flasks prior to the CSTR tests. The results of these experiments showed that no inhibition occurred.…”
Section: Methodsmentioning
confidence: 99%
“…The goals of this experiments were: (I) the determination of the ideal sulfur concentration to cover the microorganisms' necessities and, therefore, produce the highest amount of sulfuric acid, and (II) the leaching of the highest achievable zinc share while obtaining the lowest possible remaining sulfur in the already treated solid residue. Since the exposure of the microorganisms to a residue could possibly affect the microorganisms [22], batch experiments were conducted with (10, 30, 40 and 50 g/L) in 250 mL shaker flasks prior to the CSTR tests. The results of these experiments showed that no inhibition occurred.…”
Section: Methodsmentioning
confidence: 99%